One‐pot conversion of wheat straw into biobased chemicals in methanol/water medium using cheap mixed acid catalyst. (18th November 2021) - Zhao, Sibo; Huang, Xuezheng; Yan, Zhenli; Chang, Chun; Xu, Guizhuan; Du, Chaojun; Jiao, Youzhou; Chen, Zhiyong
Abstract: BACKGROUND: Environmental concerns and the diminishing availability of unrenewable resources have spurred research into the use of agricultural waste as a feedstock for industrial applications. Efficient conversion of wheat straw into biobased chemicals is an important way to realize the potential value of renewable agricultural biomass. This study investigated one‐pot conversion of wheat straw into two notable platform chemicals, levulinic acid (LA) and methyl levulinate (ML). RESULTS: A mixed acid catalyst system, including 1% H2 SO4 and 0.015 mol L –1 Al2 (SO4 )3, was an efficient catalyst for the conversion of wheat straw due to the combination of Brønsted acid and Lewis acid. A ratio of wheat straw to methanol of 5 g/50 mL was identified as the preferred solid/liquid ratio, and a methanol/H2 O medium with 25% water content aided the simultaneous production of LA and ML from wheat straw. Under optimum conditions, the maximum total yield of LA and ML reached 23.01% at 220 °C and 3 h. The kinetics of biobased chemical formation and the reaction pathways in methanol/water were investigated. CONCLUSION: The presence of water in the methanol/H2 O medium affected the distribution of products and promoted hydrolysis reactions. The methanol/H2 O medium not only inhibited the side reactions but also promoted the degradation of wheat straw and increased the total yield of LA and ML. This study provides a feasible method for the conversion of wheat straw to prepare biobased chemicals. © 2021 Society of Chemical Industry.